The The Utilization Of Homework Videotaping To Enhance The Students’ English Speaking Skills - Perdani, Yella Dezas (Bina Nusantara University, 2024)
Enhancing students' oral proficiency is a key objective of English courses, and one effective pedagogical approach is assigning video-based homework that features English conversations aligned with the curriculum. English language students encounter numerous challenges when attempting to enhance their speaking abilities. One limitation is the restricted amount of time available for in-class practice. One possible homework assignment is to create video recordings. This offers a chance for students to enhance their creativity and boost their self-assurance as the homework encompasses various elements of oral assignments, such as productivity, intention, challenge and authenticity. Hence, this webinar aims to disseminate knowledge on the specific teaching methods and procedures that teachers can implement when utilising this instructional approach. The purpose of this webinar was to provide the teachers, instructors and practitioners in the field of English education with an interactive forum for discussion. Participants will have the chance to share their experiences and ask questions, which will lead to a fruitful exchange of knowledge. Engaging in activities can yield fresh perspectives and impart useful skills that are immediately applicable to the classroom or other educational setting.